2017
DOI: 10.1176/appi.ajp.2017.16090996
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Transcranial Current Stimulation in Psychiatry

Abstract: Neurostimulation is rapidly emerging as an important treatment modality for psychiatric disorders. One of the fastest-growing and least regulated approaches to noninvasive therapeutic stimulation involves the application of weak electrical currents. Widespread enthusiasm for low-intensity transcranial electrical current stimulation (tCS) is reflected by the recent surge in direct-to-consumer device marketing, do-it-yourself enthusiasm, and an escalating number of clinical trials. In the wake of this rapid grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 75 publications
3
74
0
5
Order By: Relevance
“…Other problems are related to the diverse and multifaceted regulations in different countries and to the quality of performed trials. For example, recent findings even suggest that other electrical stimulation devices and methods that are cleared for use in psychiatric disorders are supported by low-quality data only (Philip et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Other problems are related to the diverse and multifaceted regulations in different countries and to the quality of performed trials. For example, recent findings even suggest that other electrical stimulation devices and methods that are cleared for use in psychiatric disorders are supported by low-quality data only (Philip et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Another treatment modality evidenced as necessary for BP was transcranial electrostimulation, mentioned by one of the professionals of this study. However, the use of this procedure has robust evidence of improvement in the treatment of depressive disorders, and its use in other psychiatric disorders lacks evidence (20) .…”
Section: Discussionmentioning
confidence: 99%
“…tDCS has been used for multiple health purposes [48][49][50][51][52][53]. Regarding the use of tDCS in insomnia, the role of prefronto-thalamic-cerebellar circuit on cognitive dysfunctions and sleep quality in euthymic bipolar disorder (BD) patients have showed that tDCS (2 mA) for 20 min/day during 3 consecutive weeks applied to left dorsolateral prefrontal cortex (DLPFC) and right cerebellar cortex improved sleep [54].…”
Section: Transcranial Direct Current Stimulation For Insomniamentioning
confidence: 99%